Evolutionary stability of social norms in a socio-economic equilibrium model - Hans Peter Grüner (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1994)
A hybrid of a model of economic equilibrium in two markets and a social game is formed. The link between the two is established through a social norm which conditions correct social behavior on economic variables and therefore distorts the economic equilibrium allocation. The initial endowment of an individual determines whether she gains from a social norm. The evolution of norms is examined in a dynamic model where norms are more likely to persist if they deliver higher utility to their believers. Also it is assumed that norms lose importance when they are disobeyed by their believers. Optimally coordinating norms are not necessarily evolutionarily stable and a suboptimal norm can be the outcome of the evolutionary process.
Keywords: A12; A13; D10; D61; 330